The outcome of laparoscopic management of adnexal pathology complicating pregnancies - Prasad, Nagendra; Chunchiah, Sarojamma; Nagarathnamma, R.; Chandrashekar, Nirmala; Shivananjappa, Nirupama Y.; Thampan, Sherin A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adnexal pathology found during pregnancy is relatively common and the reported incidences are population and investigation dependent. The most frequent types of adnexal masses are corpus luteum cysts, endometriomas, benign cystadenomas and mature cystic teratomas. The objective was to study the feasibility of laparoscopic management of adnexal pathology in pregnancy, maternal complications and fatal outcome. We have reported 25 cases of adnexal pathology complicating pregnancy, managed successfully laparoscopically with no maternal and fetal complications. Methods: The study is based on the outcome of laparoscopic management of adnexal pathology in 25 pregnant women over period of eight years. Laparoscopy was done using three port technique, 10 mm umbilical or supra umbilical port for optics and two lateral ports for instrumentation. Cystectomy was the most common procedure. Results: There was no intra or post-operative complication observed in the study. Successful obstetric outcome in all the patients with no complications was observed. Conclusions: Laparoscopy is preferred for exploration and treatment of adnexal masses especially between 14 to 25 weeks of gestation.